Effect of subsoiler plow leg shape, tillage depth, and tractor speed on some of field Performance Indicators and yield of oats - Aqeel Johny Nassir (University of Thi-Qar Journal of agricultural research, 2022)
A field experiment was carried out in the College of the Agriculture / University of Basra to study the effect of four types of subsoiler leg shapes, three tillage depths, and three tractor speeds in draft force, slip percentage, fuel consumption, and mean weight diameter (MWD). A randomized complete block design was used in a factorial experiment for data analysis. The results showed that the serrated edge of 45-degree angle surpassed on straight, serrated edge, 70-degree angle serrated edge, and curved in oat yield by a percentage of 2.4,18 and,21% respectively. However, serrated edge of 45-degree angle recorded less draft force, lower slip percentage, fuel consumption, and main weight mean diameter while the highest values of the previous characteristics were for the straight edge. The results showed that increasing tillage depth led to increasing slip percentage, fuel consumption, and draft force, also the previous characteristic increased with increasing forward speed. It was concluded that the best combination was obtained when using a 45-degree angle serrated edge and the speed of 2.34 km / h which gave the lowest fuel consumption of 8.11 liters/ha. Also, the 45-degree angle serrated edge at 10 cm tillage depth gave the lower fuel consumption of 8.78 liters/ha. Keywords: Subsoiler legs, draft force, fuel consumption, slip percentage, mean weight diameter, oat.